The Chistopol Prison as a Space of Political Repression (1978-1990) - Gerasimova, Elena A.; Salnikova, Alla A. (Journal of History Culture and Art Research, 2017)
The importance of the problem lies in the need for a deep, consistent and comprehensive study of the history of political repressions in the USSR as an integral part of the Soviet past. Although the history of political repression of the Stalinist period has been studied in-depth in Russian and foreign historiography, it does not cover the late Soviet period. The article discusses the history of the infamous "special" prison in Chistopol (Tatarstan), which functioned as a prison for political prisoners in 1978−1990. There has been performed the analysis of the prison’s social composition, detention regime, and daily practices of subsistence and survival. The basic approach to the problem was the method of complex analysis of different types of sources of official and personal origin and their comparative analysis. The results of the study include the characteristics of such an unexplored form of punishment of dissidents in the late Soviet Russia as imprisonment of "special purpose." It is proved that the regulatory "corrective" practices of the government and the actual practice of the prisoners’ everyday life were at times directly contrary to each other, which resulted not only in the lack of "re-education" of the "political" prisoners, but also in the growth of their number through joining of former criminal elements.